An empirical study on consumer motives and attitude towards adoption of electric vehicles in India: Policy implications for stakeholders. (June 2022) - Sahoo, Debajani; Harichandan, Sidhartha; Kar, Sanjay Kumar; S, Sreejesh
Abstract: The present study empirically investigates the motives behind users' attitude formation, behavioural intention, and word of mouth towards electric vehicles. An online survey was conducted among Indian youths who are currently using or potential users of electric vehicles. Data were collected by applying a multi-stage stratified sampling method. The structural equation modelling technique was applied to examine the hypothesized model and tested the proposed hypotheses. This study results show that while positive and social motives influence positive attitudes, the negative motives discourage and negatively affect electric vehicle adoption. The moderating impact of buyer involvement (high vs low) between motives and attitude was also tested. The study findings suggest that stakeholders can shape the motives through government policy and strategic action. Thus, this study provides directions that there is a need for subsidies and incentives, such as hassle-free registration at less cost, tax waive offs from central, state and local government, and also a strategic private-public partnership for infrastructure development to reduce negative motives and boost electric vehicles penetration. Highlights: Personal and social motives play a crucial role in adopting EV among Indian youths. Attitude mediates the linear and the nonlinear impact on consumer behavioural intentions. Promoting a balanced EV ecosystem by all stakeholders can be a solution to negative motives. Personal and social motive impacts buyer's high involvement for EV. The government policy must have a clear vision towards cost-effective EV.